ECONOMIC INSECURITY AND STRESS AS DETERMINANTS OF COVID-19 PREVENTIVE BEHAVIOUR IN DENPASAR - Gede Benny Setia Wirawan; The Angela Prisilia Taroreh; Dewa Ayu Agung Dwita Arthaningsih; Made Ayu Devi Pita Loka; Ngakan Made Ari Mahardika; Pande Putu Januraga (Indonesian Journal of Health Administration, 2021)
Background: The COVID-19 pandemic has constituted concurrent public health and economic crises. An inter-correlation between economic and public health impacts due to the COVID-19 pandemic needs to be studied to improve mitigation measures.Aims: This study identified a correlation of the economic insecurity and perceived stress with adherence to recommended preventive behaviours Methods: This across-sectional analytic study was conducted to adults in the working areas of East Denpasar Primary Healthcare Center I. Respondents were selected using consecutive sampling and given a self-administered questionnaire. The research variables included demographic characteristics, economic insecurity indicators, perceived stress, and adherence to handwashing, mask-wearing, physical distancing, and limitation on the social gathering. Correlations, linear regressions, and path analyses were conducted using IBM SPSS 23.0.Results: As many as 161 respondents of which 34.2% males were involved had a mean age of 36.31 (± 7.16) years. Sex, job insecurity, income insecurity, and perceived stress were found as independent determinants in females. Female sex and job insecurity was associated with better preventive behaviours with an adjusted β value of 0.276 and 0.306, while income insecurity and perceived stress had the opposite association with a β value of -0.247 and -0.224.Conclusion: There are correlations between economic insecurity and preventive behavioural practices during COVID-19. It is suggested that public health policies against COVID-19 cover measures of economic safety nets to improve adherenceKeywords: behaviour, COVID-19, economic insecurity, perceived stress, prevention.